InclusAÇÃO: provocações artístico-pedagógicas - Figueiredo, Lygia Maia Nobre de (2020)
The present research had as its object of study the investigation of performance as a vehicle for social inclusion through the Theater Group of the Orlando Cavalcanti Gomes State School, made up of high school students, in the Cristo neighborhood, in the city of João Pessoa (PB). Through artistic pedagogical processes, we sought to work with the participants (students) on the relationship between school environment, teaching-learning and exclusionary and inclusive processes. As an artist-teacherdisabled, the problems started with my experiences and social exclusionary processes. From this analysis, the Group felt motivated to research, identify, analyze: legislation in force in the country, theorists who could elucidate the areas of exclusion and inclusion, in pedagogical-social dimensions. Thus, the proposition of this participant research investigates performance as an inclusive methodology of pedagogical work, considering Augusto Boal's understanding of the fact that art is both a right and an obligation, a form of knowledge and enjoyment, constituting itself as a duty of citizenship and a weapon of liberation. In this sense, its use in the pedagogical scope brings a powerful possibility for empowerment and offers questions about the systems that exclude and include the various subjects. In addition, the sooner the dialogue takes place, the more revolution there will be, therefore, the urge for dialogical propositions is imperative in the school context. Using the theoretical foundations of Vygotskian psychology and Foucauldian thought, theoretical bases are related to the use of Performance as a means for dialogues / debates, construction of scenes about the processes of social exclusion / inclusion that strengthened the questions and inquiries to respect for the existence of inclusion through the Performing Arts. Thus, this research proposed to investigate the pedagogical work in Performance, according to the ideas of various thinkers, understanding the school as an intelligent collective.